Analysis and observation of grid connected single phase inverter integration - Ali Ateya, Ali Mohamed (2020)
A single-phase grid connected with a photovoltaic (PV) power system that will provide high voltage gain with state model analysis for the control of the system has been presented. In addition to the solar panels, the system is equipped with a dc–dc converter, which allows the panels’ maximum power point to be tracked, a singlephase inverter and PI controller, all connected to a single-phase utility grid. The maximum power point is maintained with a perturb and observe method. A PI controller is used to control the power injected into the grid. The controller is used to generate PWM and also controlling extra power. The maximum power delivered, and it is synchronized with help of PWM to improve the power quality and system efficiency. In this project the design separated in closed loop and open loop designs. The result in both designs are different where is the voltage will be increase up to 3.214% more in closed loop design. Also, the power will increase up to 27.78% in closed loop design.